1997
DOI: 10.1021/np9700681
|View full text |Cite
|
Sign up to set email alerts
|

Norditerpenoids and Diterpenoids from Salvia multicaulis with Antituberculous Activity

Abstract: From the roots of Salvia multicaulis, four new aromatic norditerpenoids, multicaulin (1), 12-demethylmulticauline (2), multiorthoquinone (3), and 12-demetylmultiorthoquinone (4), two new abietane diterpenoids, 12-methyl-5-dethydrohorminone (5) and 12-methyl-5-dehydroacetylhorminone (6), as well as a new pimarane diterpenoid, salvipimarone (7), were isolated. Also obtained in this investigation were the known compounds alpha-amyrin, hinokione, horminone, lupeol, manool, 1-oxoferruginol, 18-oxoferruginol, pisife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 30 publications
4
80
0
Order By: Relevance
“…The extracts have been found to have antibacterial activity (Alma et al, 2003;Amanlou et al, 2004;Digrak et al, 2001;Bozin et al, 2006;Karaman et al, 2001), antifungal activity (Bouchra et al, 2003;Askun et al, 2008;Gulluce et al, 2003;Guynot et al, 2003;Souza et al, 2005), antimycobacterial activity (Ulubelen et al, 1997;Askun et al, 2009), antioxidant activity (Alma et al, 2003Bozin et al, 2006;Mosaffa et al, 2006;Gulluce et al, 2003) and anti-inflammatory activity (Alcar´az et al, 1989;Jim´enez et al, 1986). Inhibitory effects of oregano components on some foodborne fungi were reported (Akgul & Kivanc, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The extracts have been found to have antibacterial activity (Alma et al, 2003;Amanlou et al, 2004;Digrak et al, 2001;Bozin et al, 2006;Karaman et al, 2001), antifungal activity (Bouchra et al, 2003;Askun et al, 2008;Gulluce et al, 2003;Guynot et al, 2003;Souza et al, 2005), antimycobacterial activity (Ulubelen et al, 1997;Askun et al, 2009), antioxidant activity (Alma et al, 2003Bozin et al, 2006;Mosaffa et al, 2006;Gulluce et al, 2003) and anti-inflammatory activity (Alcar´az et al, 1989;Jim´enez et al, 1986). Inhibitory effects of oregano components on some foodborne fungi were reported (Akgul & Kivanc, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…(Heath, 1981;Topcu, 2006;Celep et al, 2009). Salvia species incorporate differend secondary metabolites like diterpenoids, essential oils, sterols, flavonoids, sesquiterpenoids, sesterpenoids, and flavonoids (Ulubelen et al, 1997;Esquivel et al, 2000). The some of phenolic compounds of plants member of this genus have shown perfect antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miltirone (2) 1 is a cytotoxic natural product and contains the 3-isopropylnaphtelene-1,2-dione moiety. Ulubelen et al 2 reported that multiorthoquinone (3) and 2-demethylmultiorthoquinone (4), quinoid natural products, show very efficient anti-tuberculosis activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miltirone (2) 1 is a cytotoxic natural product and contains the 3-isopropylnaphtelene-1,2-dione moiety. Ulubelen et al 2 reported that multiorthoquinone (3) and 2-demethylmultiorthoquinone (4), quinoid natural products, show very efficient anti-tuberculosis activity. Huang et al 3 reported 1 itself and its derivatives to have remarkable cytotoxic activities against A549 and HCT-116 cell lines and to have inhibitory activity on Cdc25 phosphatases, key regulators of the cycle during normal eukaryotic cell division and mediators of the checkpoint response in cells with DNA damage.…”
Section: Introductionmentioning
confidence: 99%